A PVC fabric formula for heating pad and its production process

By adding composite plasticizer and modified nano-scale inorganic powder to the PVC fabric for heating pads, the problem of reduced brittleness of PVC materials at low temperatures is solved, the cold resistance and service life are improved, and the flame retardant performance and toughness are enhanced. .

CN115403880BActive Publication Date: 2025-02-11SHENZHEN JINLUXING TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211105558.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-09
Publication Date
2025-02-11
Estimated Expiration
2042-09-09

AI Technical Summary

Technical Problem

The brittleness of PVC materials in low temperature environments leads to problems with the cold resistance and service life of the heating pads, and the added plasticizers may volatilize and reduce performance.

Method used

Using a PVC fabric formula for heating pads, including PVC resin, composite plasticizer, composite stabilizer, modified nano-grade aluminum silicate, modified nano-grade calcium carbonate and modified nano-grade inorganic flame retardant, through modification The nano powder is cross-linked with the composite plasticizer to improve the dispersion effect and flame retardant performance.

Benefits of technology

It improves the performance of PVC materials in low temperature environments, extends service life, enhances flame retardant performance and toughness, and ensures the safety and effectiveness of the heating pad.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of heating pad materials, and in particular to a PVC fabric formula for heating pads and a production process thereof, which comprises the following components by weight: 90-100 parts of PVC resin; 40-50 parts of composite plasticizer; 1-5 parts of composite stabilizer; 1-5 parts of composite coupling agent; 1-4 parts of modified nano-scale aluminum silicate; 1-4 parts of modified nano-scale calcium carbonate; and 1-4 parts of modified nano-scale inorganic flame retardant. The poor low-temperature performance of PVC due to the migration and volatilization of plasticizers and the flammability caused by the addition of plasticizers can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heating pad materials, and in particular to a PVC fabric formula for a heating pad and a production process thereof. Background Art

[0002] PVC is the English abbreviation of polyvinyl chloride plastic. Polyvinyl chloride is a polymer formed by the polymerization of vinyl chloride monomer. Polyvinyl chloride (PVC) is one of the earliest developed, largest-produced and most widely used general-purpose plastic varieties in my country.

[0003] Due to its own molecular structure, PVC has the disadvantages of high brittleness, poor thermal stability and poor low-temperature performance. In order to solve the above-mentioned PVC defects, people usually use functional additives to improve the physical and chemical properties of PVC so as to broaden its application areas.

[0004] As a way for people to keep warm in winter, heating pads wrap around people's waists, legs and other parts that need to be kept warm. The temperature in winter can reach -45℃, and historical records show it is even as low as -58℃. At this time, the toughness of PVC is greatly reduced, and it is easy to break when bent, exposing the internal heater, which may burn the human body and pose a fire hazard, making it not conducive to people's use.

[0005] In order to improve the low-temperature brittleness problem of PVC, a low-temperature brittle-resistant PVC composite material and a processing method are disclosed in Chinese Patent Publication No. 113105699, in which a low-temperature brittle agent is added to the PVC resin to improve the low-temperature resistance of PVC. However, the low-temperature brittle agent added is a small molecule additive, which will gradually migrate out of the PVC product over time and evaporate into the air, making the cold resistance worse and worse. At the same time, the PVC material becomes hard and brittle, reducing the service life of the heating pad, thereby losing its use value.

[0006] For example, Chinese Patent Publication No. 105255061 discloses an environmentally friendly soft PVC plasticizer. Although it is a macromolecular plasticizer composed of a variety of mixtures and has mobility comparable to that of small molecular plasticizers, it is unknown how it has no mobility, no volatility, and how it improves the low-temperature brittleness of PVC.

[0007] PVC itself has good flame retardant properties. In order to improve other physical and chemical properties, the added plasticizer is usually a flammable substance, which greatly weakens the flame retardant properties of PVC materials. For this reason, flame retardants are usually added to PVC to achieve the purpose of flame retardancy. Common flame retardants include halogen flame retardants. Halogen flame retardants have cheap raw materials and high flame retardant efficiency, but due to the problem of dioxins, they are highly carcinogenic, and halogen flame retardants emit a large amount of hydrogen halide smoke when burning, which is extremely corrosive and causes secondary harm to people. For this reason, inorganic flame retardants have the advantages of being smokeless, low in temperature, and high in heat resistance.

[0008] For example, the flame retardant for PVC processing and its preparation method, and the flame retardant power pipe containing the flame retardant disclosed in China Patent Publication No. 113444291 use modified β-cyclodextrin to coat the inorganic flame retardant to solve the problem that excessive inorganic flame retardant is difficult to mix evenly in the PVC system, but it is usually the physical and chemical properties of modified PVC. By weight, 50-60 parts of plasticizer will be added to 100 parts of PVC resin. In this patent, only 5 parts of plasticizer are added to 100 parts of PVC resin. It can be predicted that when the same proportion of plasticizer is added, its flame retardant performance will decrease, and it is difficult to meet the requirements of use as a heating pad.

[0009] Therefore, it is urgent to develop a PVC material and process that meets the requirements of a heating pad to improve the above-mentioned defects. Summary of the invention

[0010] The first object of the present invention is to provide a PVC fabric formula for a heating pad, which can improve the poor low-temperature performance of PVC due to the migration and volatilization of plasticizers, as well as the flammability problem caused by the addition of plasticizers.

[0011] A PVC fabric formula for a heating pad comprises the following components by weight:

[0012] PVC resin: 90-100 parts;

[0013] Composite plasticizer: 40-50 parts;

[0014] Composite stabilizer: 1-5 parts;

[0015] Composite coupling agent: 1-5 parts;

[0016] Modified nano-aluminum silicate: 1-4 parts;

[0017] Modified nano-scale calcium carbonate: 1-4 parts;

[0018] Modified nano-scale inorganic flame retardant: 1-4 parts.

[0019] Preferably, the composite plasticizer includes a cold-resistant plasticizer and a macromolecular plasticizer in a weight ratio of 0.25:1-1:4, the cold-resistant plasticizer is one of dioctyl phthalate, diisooctyl phthalate, diisodecyl phthalate, diisononyl phthalate, dibutyl phthalate, diisobutyl phthalate, dimethyl phthalate, diethyl phthalate, dicyclohexyl phthalate, dioctyl terephthalate, adipic acid esters and sebacates, and the macromolecular plasticizer is one of the polyester plasticizers.

[0020] Preferably, the composite coupling agent is any combination of a silane coupling agent, an aluminate coupling agent, a rare earth coupling agent, and an aluminum-titanium coupling agent.

[0021] Preferably, the modified nano-scale inorganic flame retardant is at least one of modified nano-scale antimony trioxide, modified nano-scale magnesium hydroxide, modified nano-scale aluminum hydroxide, and modified nano-scale red phosphorus.

[0022] Preferably, the modified nano-scale aluminum silicate is prepared by: grinding the nano-scale aluminum silicate into a nano-grinder at least once to obtain the modified nano-scale aluminum silicate;

[0023] Preparation of the modified nano-scale calcium carbonate: putting the nano-scale calcium carbonate into a nano-grinder at least once for grinding to obtain the modified nano-scale calcium carbonate;

[0024] Preparation of the modified nano-scale inorganic flame retardant: The nano-scale inorganic flame retardant is put into a nano-grinder at least once for grinding to obtain the modified nano-scale inorganic flame retardant.

[0025] The second purpose of the present invention is to provide a production process of a PVC fabric formula for a heating pad, which can fully disperse various additives in the PVC resin and ultimately improve the quality of the finished heating pad.

[0026] A production process of a PVC fabric formula for a heating pad includes the following preparation steps:

[0027] S1: mixing and dispersing modified nano-scale aluminum silicate, modified nano-scale calcium carbonate, and modified nano-scale inorganic flame retardant to obtain a mixed inorganic powder;

[0028] S2: Surface treatment of the mixed inorganic powder in S1 after hydrolysis with 50% of the composite coupling agent to obtain a modified mixed inorganic powder;

[0029] S3: Put the PVC resin, composite plasticizer, composite stabilizer, composite coupling agent, modified mixed inorganic powder in S2, and pigment into a drying oven for drying;

[0030] S4: the dried PVC resin, the composite stabilizer, the remaining 50% of the composite coupling agent, and 70% of the modified mixed inorganic powder in S3 are mixed in a high-speed kneader and stirred and mixed uniformly to obtain a first mixed material; the remaining 30% of the modified mixed inorganic powder and the composite plasticizer are mixed in a high-speed kneader and stirred and mixed uniformly to obtain a second mixed material;

[0031] S5: putting the second mixed material in S4 into an internal mixer for preliminary plasticization;

[0032] S6: putting the first mixed material in S4 into the internal mixer in S5 and heating it with the second mixed material, and continuing to plasticize to obtain a molten material;

[0033] S7: heating the molten material in S6 until it is completely plasticized and begins to be used for feeding;

[0034] S8: removing impurities from the completely plasticized molten material in S7 through a filter screen;

[0035] S9: the molten material from which impurities are removed in S8 is extruded through an extruder and sent to a casting machine, and pressed to a desired thickness to form a film;

[0036] S10: pulling the film in S9 onto the embossing wheel;

[0037] S11: Cooling the film after embossing in S10 through a cooling mechanism;

[0038] S12: rolling up the film cooled in S11 and placing it for cooling and solidification;

[0039] S13: Cut the film cured in S12 into required specifications to obtain a finished heating pad fabric.

[0040] By adopting the above technical scheme, the inorganic powder is first cross-linked with a composite plasticizer consisting of a macromolecular plasticizer and a cold-resistant plasticizer to increase the molecular weight and flame retardancy of the cold-resistant plasticizer, and then added to the PVC resin, the dispersion effect can be improved, which is beneficial to the mechanical strength of the finished PVC.

[0041] In summary, the beneficial effects of this application are:

[0042] The invention provides a PVC fabric formula for a heating pad and a production process thereof. PVC resin is used as a main raw material. Compared with a monomer stabilizer, a composite stabilizer is added to have a good synergistic effect to prevent the degradation of PVC and to improve the service life of the product. The modified nano-scale aluminum silicate can improve the wear resistance of the fabric for the heating pad and act as a white coating, while increasing the dispersibility and stability of the pigment to improve the hiding power of the pigment. The modified nano-scale calcium carbonate has higher surface activity due to the small-scale effect, can be evenly filled in the dispersed PVC resin, and can improve the toughness and hardness of the PVC resin. The calcium carbonate is decomposed by heat to produce carbon dioxide, which has a certain promoting effect on flame retardancy, and the calcium oxide produced can absorb acidic gases by hand to reduce the damage to the human body and the environment. The modified nano-inorganic flame retardant is non-toxic and harmless, and can decompose substances to absorb heat, slowing down the polyvinyl chloride. The decomposition rate of olefins; the composite coupling agent can produce a synergistic effect to strengthen the modification of the particle surface in the mixed inorganic powder, so that the modified mixed inorganic powder is better compatible with the resin and the composite plasticizer, and the low-temperature performance of the PVC resin is improved; the composite plasticizer is composed of a small molecule cold-resistant plasticizer and a large molecule polyester plasticizer, and is first plasticized with the modified mixed inorganic powder to cross-link the mixed inorganic powder with the composite plasticizer, and the modified mixed inorganic powder can be used for heat storage and heat conduction, which plays a certain flame retardant role. The molecular weight of the plasticizer reduces the rate of migration and diffusion, thereby ensuring the performance of PVC in a low-temperature environment, and at the same time cross-links with each other to reduce the distance between molecules. Under the action of van der Waals force, the density of the PVC film is further improved, so that the finished heating pad fabric has good toughness and tensile resistance. DETAILED DESCRIPTION

[0043] It should be noted that in this application document, pigments are added to the fabric of the heating pad, and the addition of pigments changes the color of the resin to meet people's aesthetic needs.

[0044] It should be noted that, in the present application document, the term "modification" refers to modifying the inorganic powder by physical grinding, so that the particle size of the modified inorganic powder is smaller than that of the inorganic powder before grinding, and the range of particle sizes tends to be consistent.

[0045] Example 1

[0046] A PVC fabric formula for a heating pad comprises the following components by weight:

[0047] PVC resin: 90 parts;

[0048] Dioctyl phthalate: 20 parts;

[0049] Poly(dioctyl adipate): 20 parts;

[0050] Composite stabilizer: 1 part;

[0051] Silane coupling agent: 0.5 parts;

[0052] Rare earth coupling agent: 0.5 parts;

[0053] Modified nano-aluminum silicate: 1 part;

[0054] Modified nano-scale calcium carbonate: 1 part;

[0055] Modified nano-magnesium hydroxide: 0.5 parts;

[0056] Modified nano-aluminum hydroxide: 0.5 parts;

[0057] Pigment: 1 part.

[0058] Preparation of the modified nano-scale aluminum silicate: putting the nano-scale aluminum silicate into a nano-grinder at least once for grinding to obtain the modified nano-scale aluminum silicate;

[0059] Preparation of the modified nano-scale calcium carbonate: putting the nano-scale calcium carbonate into a nano-grinder at least once for grinding to obtain the modified nano-scale calcium carbonate;

[0060] Preparation of the modified nano-scale inorganic flame retardant: The nano-scale inorganic flame retardant is put into a nano-grinder at least once for grinding to obtain the modified nano-scale inorganic flame retardant.

[0061] Prepared by the following steps:

[0062] S1: mixing and dispersing modified nano-scale aluminum silicate, modified nano-scale calcium carbonate, and modified nano-scale inorganic flame retardant to obtain a mixed inorganic powder;

[0063] S2: Surface treatment of the mixed inorganic powder in S1 after hydrolysis with 50% of the composite coupling agent to obtain a modified mixed inorganic powder;

[0064] S3: Put the PVC resin, composite plasticizer, composite stabilizer, composite coupling agent, modified mixed inorganic powder in S2, and pigment into a drying oven for drying;

[0065] S4: the dried PVC resin, the composite stabilizer, the remaining 50% of the composite coupling agent, and 70% of the modified mixed inorganic powder in S3 are mixed in a high-speed kneader and stirred and mixed uniformly to obtain a first mixed material; the remaining 30% of the modified mixed inorganic powder and the composite plasticizer are mixed in a high-speed kneader and stirred and mixed uniformly to obtain a second mixed material;

[0066] S5: putting the second mixed material in S4 into an internal mixer for preliminary plasticization;

[0067] S6: putting the first mixed material in S4 into the internal mixer in S5 and heating it with the second mixed material, and continuing to plasticize to obtain a molten material;

[0068] S7: heating the molten material in S6 until it is completely plasticized and begins to be used for feeding;

[0069] S8: removing impurities from the completely plasticized molten material in S7 through a filter screen;

[0070] S9: the molten material from which impurities are removed in S8 is extruded through an extruder and sent to a casting machine, and pressed to a desired thickness to form a film;

[0071] S10: pulling the film in S9 onto the embossing wheel;

[0072] S11: Cooling the film after embossing in S10 through a cooling mechanism;

[0073] S12: rolling up the film cooled in S11 and placing it for cooling and solidification;

[0074] S13: Cut the film cured in S12 into required specifications to obtain a finished heating pad fabric.

[0075] Example 2

[0076] PVC resin: 95 parts;

[0077] Dioctyl phthalate: 22.5 parts;

[0078] Poly(dioctyl adipate): 22.5 parts;

[0079] Composite stabilizer: 3 parts;

[0080] Silane coupling agent: 1.5 parts;

[0081] Rare earth coupling agent: 1.5 parts;

[0082] Modified nano-aluminum silicate: 3 parts;

[0083] Modified nano-scale calcium carbonate: 3 parts;

[0084] Modified nano-magnesium hydroxide: 1.5 parts;

[0085] Modified nano-aluminum hydroxide: 1.5 parts;

[0086] Pigment: 3 parts.

[0087] Preparation of the modified nano-scale aluminum silicate: putting the nano-scale aluminum silicate into a nano-grinder at least once for grinding to obtain the modified nano-scale aluminum silicate;

[0088] Preparation of the modified nano-scale calcium carbonate: putting the nano-scale calcium carbonate into a nano-grinder at least once for grinding to obtain the modified nano-scale calcium carbonate;

[0089] Preparation of the modified nano-scale inorganic flame retardant: The nano-scale inorganic flame retardant is put into a nano-grinder at least once for grinding to obtain the modified nano-scale inorganic flame retardant.

[0090] Prepared by the following steps:

[0091] S1: mixing and dispersing modified nano-scale aluminum silicate, modified nano-scale calcium carbonate, and modified nano-scale inorganic flame retardant to obtain a mixed inorganic powder;

[0092] S2: Surface treatment of the mixed inorganic powder in S1 after hydrolysis with 50% of the composite coupling agent to obtain a modified mixed inorganic powder;

[0093] S3: Put the PVC resin, composite plasticizer, composite stabilizer, composite coupling agent, modified mixed inorganic powder in S2, and pigment into a drying oven for drying;

[0094] S4: the dried PVC resin, the composite stabilizer, the remaining 50% of the composite coupling agent, and 70% of the modified mixed inorganic powder in S3 are mixed in a high-speed kneader and stirred and mixed uniformly to obtain a first mixed material; the remaining 30% of the modified mixed inorganic powder and the composite plasticizer are mixed in a high-speed kneader and stirred and mixed uniformly to obtain a second mixed material;

[0095] S5: putting the second mixed material in S4 into an internal mixer for preliminary plasticization;

[0096] S6: putting the first mixed material in S4 into the internal mixer in S5 and heating it with the second mixed material, and continuing to plasticize to obtain a molten material;

[0097] S7: heating the molten material in S6 until it is completely plasticized and begins to be used for feeding;

[0098] S8: removing impurities from the completely plasticized molten material in S7 through a filter screen;

[0099] S9: the molten material from which impurities are removed in S8 is extruded through an extruder and sent to a casting machine, and pressed to a desired thickness to form a film;

[0100] S10: pulling the film in S9 onto the embossing wheel;

[0101] S11: Cooling the film after embossing in S10 through a cooling mechanism;

[0102] S12: rolling up the film cooled in S11 and placing it for cooling and solidification;

[0103] S13: Cut the film cured in S12 into required specifications to obtain a finished heating pad fabric.

[0104] Example 3

[0105] PVC resin: 100 parts;

[0106] Dioctyl phthalate: 25 parts;

[0107] Poly(dioctyl adipate): 25 parts;

[0108] Composite stabilizer: 5 parts;

[0109] Silane coupling agent: 2.5 parts;

[0110] Rare earth coupling agent: 2.5 parts;

[0111] Modified nano-aluminum silicate: 5 parts;

[0112] Modified nano-scale calcium carbonate: 5 parts;

[0113] Modified nano-magnesium hydroxide: 2.5 parts;

[0114] Modified nano-aluminum hydroxide: 2.5 parts;

[0115] Pigment: 5 parts.

[0116] The modified nano-scale inorganic flame retardant is at least one of modified nano-scale antimony trioxide, modified nano-scale magnesium hydroxide, modified nano-scale aluminum hydroxide and modified nano-scale red phosphorus.

[0117] Preparation of the modified nano-scale aluminum silicate: putting the nano-scale aluminum silicate into a nano-grinder at least once for grinding to obtain the modified nano-scale aluminum silicate;

[0118] Preparation of the modified nano-scale calcium carbonate: putting the nano-scale calcium carbonate into a nano-grinder at least once for grinding to obtain the modified nano-scale calcium carbonate;

[0119] Preparation of the modified nano-scale inorganic flame retardant: The nano-scale inorganic flame retardant is put into a nano-grinder at least once for grinding to obtain the modified nano-scale inorganic flame retardant.

[0120] Prepared by the following steps:

[0121] S1: mixing and dispersing modified nano-scale aluminum silicate, modified nano-scale calcium carbonate, and modified nano-scale inorganic flame retardant to obtain a mixed inorganic powder;

[0122] S2: Surface treatment of the mixed inorganic powder in S1 after hydrolysis with 50% of the composite coupling agent to obtain a modified mixed inorganic powder;

[0123] S3: Put the PVC resin, composite plasticizer, composite stabilizer, composite coupling agent, modified mixed inorganic powder in S2, and pigment into a drying oven for drying;

[0124] S4: the dried PVC resin, the composite stabilizer, the remaining 50% of the composite coupling agent, and 70% of the modified mixed inorganic powder in S3 are mixed in a high-speed kneader and stirred and mixed uniformly to obtain a first mixed material; the remaining 30% of the modified mixed inorganic powder and the composite plasticizer are mixed in a high-speed kneader and stirred and mixed uniformly to obtain a second mixed material;

[0125] S5: putting the second mixed material in S4 into an internal mixer for preliminary plasticization;

[0126] S6: putting the first mixed material in S4 into the internal mixer in S5 and heating it with the second mixed material, and continuing to plasticize to obtain a molten material;

[0127] S7: heating the molten material in S6 until it is completely plasticized and begins to be used for feeding;

[0128] S8: removing impurities from the completely plasticized molten material in S7 through a filter screen;

[0129] S9: the molten material from which impurities are removed in S8 is extruded through an extruder and sent to a casting machine, and pressed to a desired thickness to form a film;

[0130] S10: pulling the film in S9 onto the embossing wheel;

[0131] S11: Cooling the film after embossing in S10 through a cooling mechanism;

[0132] S12: rolling up the film cooled in S11 and placing it for cooling and solidification;

[0133] S13: Cut the film cured in S12 into required specifications to obtain a finished heating pad fabric.

[0134] Comparative Example 1

[0135] PVC resin: 95 parts;

[0136] Dioctyl phthalate: 45 parts;

[0137] Composite stabilizer: 3 parts;

[0138] Silane coupling agent: 1.5 parts;

[0139] Rare earth coupling agent: 1.5 parts;

[0140] Modified nano-aluminum silicate: 3 parts;

[0141] Modified nano-scale calcium carbonate: 3 parts;

[0142] Modified nano-magnesium hydroxide: 1.5 parts;

[0143] Modified nano-aluminum hydroxide: 1.5 parts;

[0144] Pigment: 3 parts.

[0145] Preparation of the modified nano-scale aluminum silicate: putting the nano-scale aluminum silicate into a nano-grinder at least once for grinding to obtain the modified nano-scale aluminum silicate;

[0146] Preparation of the modified nano-scale calcium carbonate: putting the nano-scale calcium carbonate into a nano-grinder at least once for grinding to obtain the modified nano-scale calcium carbonate;

[0147] Preparation of the modified nano-scale inorganic flame retardant: The nano-scale inorganic flame retardant is put into a nano-grinder at least once for grinding to obtain the modified nano-scale inorganic flame retardant.

[0148] Prepared by the following steps:

[0149] S1: mixing and dispersing modified nano-scale aluminum silicate, modified nano-scale calcium carbonate, and modified nano-scale inorganic flame retardant to obtain a mixed inorganic powder;

[0150] S2: Surface treatment of the mixed inorganic powder in S1 after hydrolysis with 50% of the composite coupling agent to obtain a modified mixed inorganic powder;

[0151] S3: Put the PVC resin, cold-resistant plasticizer, composite stabilizer, composite coupling agent, modified mixed inorganic powder in S2, and pigment into a drying oven for drying;

[0152] S4: the dried PVC resin, the composite stabilizer, the remaining 50% of the composite coupling agent, and 70% of the modified mixed inorganic powder in S3 are mixed in a high-speed kneader and stirred and mixed uniformly to obtain a first mixed material; the remaining 30% of the modified mixed inorganic powder and the cold-resistant plasticizer are mixed in a high-speed kneader and stirred and mixed uniformly to obtain a second mixed material;

[0153] S5: putting the second mixed material in S4 into an internal mixer for preliminary plasticization;

[0154] S6: putting the first mixed material in S4 into the internal mixer in S5 and heating it with the second mixed material, and continuing to plasticize to obtain a molten material;

[0155] S7: heating the molten material in S6 until it is completely plasticized and begins to be used for feeding;

[0156] S8: removing impurities from the completely plasticized molten material in S7 through a filter screen;

[0157] S9: the molten material from which impurities are removed in S8 is extruded through an extruder and sent to a casting machine, and pressed to a desired thickness to form a film;

[0158] S10: pulling the film in S9 onto the embossing wheel;

[0159] S11: Cooling the film after embossing in S10 through a cooling mechanism;

[0160] S12: rolling up the film cooled in S11 and placing it for cooling and solidification;

[0161] S13: Cut the film cured in S12 into required specifications to obtain a finished heating pad fabric.

[0162] Comparative Example 2

[0163] PVC resin: 95 parts;

[0164] Dioctyl phthalate: 22.5 parts;

[0165] Poly(dioctyl adipate): 22.5 parts;

[0166] Composite stabilizer: 3 parts;

[0167] Silane coupling agent: 1.5 parts;

[0168] Rare earth coupling agent: 1.5 parts;

[0169] Modified nano-aluminum silicate: 3 parts;

[0170] Modified nano-scale calcium carbonate: 3 parts;

[0171] Modified nano-magnesium hydroxide: 1.5 parts;

[0172] Modified nano-aluminum hydroxide: 1.5 parts;

[0173] Pigment: 3 parts.

[0174] Preparation of the modified nano-scale aluminum silicate: putting the nano-scale aluminum silicate into a nano-grinder at least once for grinding to obtain the modified nano-scale aluminum silicate;

[0175] Preparation of the modified nano-scale calcium carbonate: putting the nano-scale calcium carbonate into a nano-grinder at least once for grinding to obtain the modified nano-scale calcium carbonate;

[0176] Preparation of the modified nano-scale inorganic flame retardant: The nano-scale inorganic flame retardant is put into a nano-grinder at least once for grinding to obtain the modified nano-scale inorganic flame retardant.

[0177] Prepared by the following steps:

[0178] S1: mixing and dispersing modified nano-scale aluminum silicate, modified nano-scale calcium carbonate, and modified nano-scale inorganic flame retardant to obtain a mixed inorganic powder;

[0179] S2: Put the PVC resin, composite plasticizer, composite stabilizer, composite coupling agent, mixed inorganic powder and pigment in S1 into a drying oven for drying;

[0180] S3: The dried PVC resin, composite stabilizer, composite plasticizer, composite coupling agent and mixed inorganic powder in S2 are mixed in a high-speed kneader and stirred to obtain a mixed material;

[0181] S4: putting the mixed material in S3 into an internal mixer for preliminary plasticization;

[0182] S5: continuing to heat and plasticize the mixed material in S4 to obtain a molten material;

[0183] S6: heating the molten material in S5 until it is completely plasticized and begins to be used for feeding;

[0184] S7: passing the completely plasticized molten material in S6 through a filter to remove impurities;

[0185] S8: The molten material from which impurities are removed in S7 is extruded through an extruder and sent to a casting machine, and pressed to a desired thickness to form a film;

[0186] S9: pulling the film in S8 onto the embossing wheel;

[0187] S10: Cooling the film after embossing in S9 through a cooling mechanism;

[0188] S11: rolling up the film cooled in S10 and placing it for cooling and solidification;

[0189] S12: Cut the film cured in S11 into required specifications to obtain a finished heating pad fabric.

[0190] Comparative Example 3

[0191] PVC resin: 95 parts;

[0192] Dioctyl phthalate: 22.5 parts;

[0193] Poly(dioctyl adipate): 22.5 parts;

[0194] Composite stabilizer: 3 parts;

[0195] Silane coupling agent: 1.5 parts;

[0196] Rare earth coupling agent: 1.5 parts;

[0197] Modified nano-aluminum silicate: 3 parts;

[0198] Modified nano-scale calcium carbonate: 3 parts;

[0199] Modified nano-magnesium hydroxide: 1.5 parts;

[0200] Modified nano-aluminum hydroxide: 1.5 parts;

[0201] Pigment: 3 parts.

[0202] Preparation of the modified nano-scale aluminum silicate: putting the nano-scale aluminum silicate into a nano-grinder at least once for grinding to obtain the modified nano-scale aluminum silicate;

[0203] Preparation of the modified nano-scale calcium carbonate: putting the nano-scale calcium carbonate into a nano-grinder at least once for grinding to obtain the modified nano-scale calcium carbonate;

[0204] Preparation of the modified nano-scale inorganic flame retardant: The nano-scale inorganic flame retardant is put into a nano-grinder at least once for grinding to obtain the modified nano-scale inorganic flame retardant.

[0205] Prepared by the following steps:

[0206] S1: mixing and dispersing modified nano-scale aluminum silicate, modified nano-scale calcium carbonate, and modified nano-scale inorganic flame retardant to obtain a mixed inorganic powder;

[0207] S2: Surface treatment of the mixed inorganic powder in S1 after hydrolysis with 50% of the composite coupling agent to obtain a modified mixed inorganic powder;

[0208] S3: Put the PVC resin, composite plasticizer, composite stabilizer, composite coupling agent, modified mixed inorganic powder in S2, and pigment into a drying oven for drying;

[0209] S4: the dried PVC resin, the composite stabilizer and the remaining 50% of the composite coupling agent in S3 are mixed and put into a high-speed kneader for stirring and mixing uniformly to obtain a first mixed material; all the modified mixed inorganic powders and the composite plasticizer are mixed and put into a high-speed kneader for stirring and mixing uniformly to obtain a second mixed material;

[0210] S5: putting the second mixed material in S4 into an internal mixer for preliminary plasticization;

[0211] S6: putting the first mixed material in S4 into the internal mixer in S5 and heating it with the second mixed material, and continuing to plasticize to obtain a molten material;

[0212] S7: heating the molten material in S6 until it is completely plasticized and begins to be used for feeding;

[0213] S8: removing impurities from the completely plasticized molten material in S7 through a filter screen;

[0214] S9: the molten material from which impurities are removed in S8 is extruded through an extruder and sent to a casting machine, and pressed to a desired thickness to form a film;

[0215] S10: pulling the film in S9 onto the embossing wheel;

[0216] S11: Cooling the film after embossing in S10 through a cooling mechanism;

[0217] S12: rolling up the film cooled in S11 and placing it for cooling and solidification;

[0218] S13: Cut the film cured in S12 into required specifications to obtain a finished heating pad fabric.

[0219] Comparative Example 4

[0220] PVC resin: 95 parts;

[0221] Dioctyl phthalate: 22.5 parts;

[0222] Poly(dioctyl adipate): 22.5 parts;

[0223] Composite stabilizer: 3 parts;

[0224] Silane coupling agent: 3 parts;

[0225] Modified nano-aluminum silicate: 3 parts;

[0226] Modified nano-scale calcium carbonate: 3 parts;

[0227] Modified nano-magnesium hydroxide: 1.5 parts;

[0228] Modified nano-aluminum hydroxide: 1.5 parts;

[0229] Pigment: 3 parts.

[0230] Preparation of the modified nano-scale aluminum silicate: putting the nano-scale aluminum silicate into a nano-grinder at least once for grinding to obtain the modified nano-scale aluminum silicate;

[0231] Preparation of the modified nano-scale calcium carbonate: putting the nano-scale calcium carbonate into a nano-grinder at least once for grinding to obtain the modified nano-scale calcium carbonate;

[0232] Preparation of the modified nano-scale inorganic flame retardant: The nano-scale inorganic flame retardant is put into a nano-grinder at least once for grinding to obtain the modified nano-scale inorganic flame retardant.

[0233] Prepared by the following steps:

[0234] S1: mixing and dispersing modified nano-scale aluminum silicate, modified nano-scale calcium carbonate, and modified nano-scale inorganic flame retardant to obtain a mixed inorganic powder;

[0235] S2: Surface treatment of the mixed inorganic powder in S1 after hydrolysis with 50% silane coupling agent to obtain modified mixed inorganic powder;

[0236] S3: Put the PVC resin, composite plasticizer, composite stabilizer, silane coupling agent, modified mixed inorganic powder in S2, and pigment into a drying oven for drying;

[0237] S4: the dried PVC resin, the composite stabilizer, the remaining 50% of the silane coupling agent, and 70% of the modified mixed inorganic powder in S3 are mixed in a high-speed kneader and stirred and mixed uniformly to obtain a first mixed material; the remaining 30% of the modified mixed inorganic powder and the composite plasticizer are mixed in a high-speed kneader and stirred and mixed uniformly to obtain a second mixed material;

[0238] S5: putting the second mixed material in S4 into an internal mixer for preliminary plasticization;

[0239] S6: putting the first mixed material in S4 into the internal mixer in S5 and heating it with the second mixed material, and continuing to plasticize to obtain a molten material;

[0240] S7: heating the molten material in S6 until it is completely plasticized and begins to be used for feeding;

[0241] S8: removing impurities from the completely plasticized molten material in S7 through a filter screen;

[0242] S9: the molten material from which impurities are removed in S8 is extruded through an extruder and sent to a casting machine, and pressed to a desired thickness to form a film;

[0243] S10: pulling the film in S9 onto the embossing wheel;

[0244] S11: Cooling the film after embossing in S10 through a cooling mechanism;

[0245] S12: rolling up the film cooled in S11 and placing it for cooling and solidification;

[0246] S13: Cut the film cured in S12 into required specifications to obtain a finished heating pad fabric.

[0247]

[0248]

[0249] Tables 1 and 2 above are tests on the fabric samples for heating pads prepared in Examples 1-3 and Comparative Examples 1-4 above.

[0250] From the above examples 1-3 in Table 1, it can be concluded that with the increase of each component, the various properties of the finished film are gradually improved; from the above example 2 in Table 1 compared with the comparative example 1 in Table 2, it can be concluded that the tear strength and oxygen index of the composite plasticizer composed of the macromolecular plasticizer and the cold-resistant plasticizer are improved, and the brittle temperature is slightly insufficient; from the above example 2 in Table 1 compared with the comparative example 2 in Table 2, the tear strength is slightly improved, the brittle temperature and the oxygen index are greatly reduced, and the filling of the mixed inorganic powder into the PVC resin greatly improves the tear strength of the PVC; from the above example 2 in Table 1 compared with the comparative example 3 in Table 2, the oxygen index is slightly improved, the brittle temperature and the tear strength are greatly reduced, and the mixed inorganic powder is cross-linked with the composite coupling agent, thereby improving the oxygen index of the composite plasticizer and further improving the overall oxygen index, but at the expense of the overall tear strength and brittle temperature caused by the decrease; from the above example 2 in Table 1 compared with the comparative example 4 in Table 2, the effect of using a single coupling agent is much smaller than the cross-linking effect of the composite coupling agent.

[0251] The embodiments described above are only preferred implementation modes of the present invention and cannot be used to limit the protection scope of the present invention. Any non-substantial changes and modifications made by those skilled in the art on the basis of the present invention shall fall within the protection scope of the present invention.

Claims

1. A PVC fabric for a heating pad, characterized in that: By weight, it includes the following components: PVC resin: 90-100 parts; Composite plasticizer: 40-50 parts; Composite stabilizer: 1-5 parts; Composite coupling agent: 1-5 parts; Modified nano-aluminum silicate: 1-4 parts; Modified nano-scale calcium carbonate: 1-4 parts; Modified nano-scale inorganic flame retardant: 1-4 parts; The fabric is prepared by the following steps: S1: mixing and dispersing modified nano-scale aluminum silicate, modified nano-scale calcium carbonate, and modified nano-scale inorganic flame retardant to obtain a mixed inorganic powder; S2: Surface treatment of the mixed inorganic powder in S1 after hydrolysis with 50% of the composite coupling agent to obtain a modified mixed inorganic powder; S3: putting PVC resin, composite plasticizer, composite stabilizer, composite coupling agent, modified mixed inorganic powder in S2, and pigment into a drying oven for drying; S4: the dried PVC resin, the composite stabilizer, the remaining 50% of the composite coupling agent, and 70% of the modified mixed inorganic powder in S3 are mixed in a high-speed kneader and stirred and mixed uniformly to obtain a first mixed material; the remaining 30% of the modified mixed inorganic powder and the composite plasticizer are mixed in a high-speed kneader and stirred and mixed uniformly to obtain a second mixed material; S5: putting the second mixed material in S4 into an internal mixer for preliminary plasticization; S6: putting the first mixed material in S4 into the internal mixer in S5 and heating it with the second mixed material, and continuing to plasticize to obtain a molten material; S7: heating the molten material in S6 until it is completely plasticized and begins to be used for feeding; S8: removing impurities from the completely plasticized molten material in S7 through a filter screen; S9: the molten material from which impurities are removed in S8 is extruded through an extruder and sent to a casting machine, and pressed to a desired thickness to form a film; S10: pulling the film in S9 onto the embossing wheel; S11: Cooling the film after embossing in S10 through a cooling mechanism; S12: rolling up the film cooled in S11 and placing it for cooling and solidification; S13: cutting the film cured in S12 into required specifications, thereby obtaining a finished heating pad fabric; The composite plasticizer comprises a cold-resistant plasticizer and a macromolecular plasticizer in a weight ratio of 0.25:1-1:4, the cold-resistant plasticizer is one of dioctyl phthalate, diisooctyl phthalate, diisodecyl phthalate, diisononyl phthalate, dibutyl phthalate, diisobutyl phthalate, dimethyl phthalate, diethyl phthalate, dicyclohexyl phthalate, dioctyl terephthalate, adipic acid esters and sebacates, and the macromolecular plasticizer is one of polyester plasticizers; The composite coupling agent is any combination of a silane coupling agent, an aluminate coupling agent, a rare earth coupling agent, and an aluminum-titanium coupling agent.

2. The PVC fabric for a heating pad according to claim 1, characterized in that: The modified nano-scale inorganic flame retardant is at least one of modified nano-scale antimony trioxide, modified nano-scale magnesium hydroxide, modified nano-scale aluminum hydroxide and modified nano-scale red phosphorus.

3. The PVC fabric for a heating pad according to claim 1, characterized in that: Preparation of the modified nano-scale aluminum silicate: putting the nano-scale aluminum silicate into a nano-grinder at least once for grinding to obtain the modified nano-scale aluminum silicate; Preparation of the modified nano-scale calcium carbonate: putting the nano-scale calcium carbonate into a nano-grinder at least once for grinding to obtain the modified nano-scale calcium carbonate; Preparation of the modified nano-scale inorganic flame retardant: The nano-scale inorganic flame retardant is put into a nano-grinder at least once for grinding to obtain the modified nano-scale inorganic flame retardant.

Citation Information

Patent Citations

  • Super-wide environmental-friendly decorative film material and preparation technology thereof

    CN103059473A

  • Migration-resistant environment-friendly PVC (Polyvinyl Chloride) modified material and preparation method thereof

    CN104109323A

  • Flame retardant NBR (nitrile-butadiene rubber) / CPVC (chlorinated polyvinyl chloride) plastic foaming thermal-insulation material composition

    CN104250388A

  • Nano-calcium carbonate modification method and application of nano-calcium carbonate to PVC (polyvinyl chloride) pipe reinforcement

    CN108794810A